Understanding evolutionary processes in bird species using genome-wide sequence analysis - Eltayeb, Muhammad Alfatih; Tumian, Afidalina (2017)
Meiotic recombination is the driving force behind genetic diversity. It happens non-randomly across the genome, with high concentrations in regions called recombination hot spots. Across mammalian species, PRDM9 has shown to be an important player in localizing almost all meiotic recombination hot spots. However in some species such as birds and dogs, it is discovered that the localization of hot spots is unlikely to be regulated by PRDM9 due to disruption to its coding sequence. The rapid evolution of PRDM9 maybe a response to escape the self-disruptive drive called biased gene conversion (BGC). In this paper, we attempt to uncover if we can see any signatures of BGC in bird species by using alignment data consisting of the chicken, domestic turkey, zebra finch and the green anole. By studying relative motif losses and gains across the genomes, we aim to understand the biases and target sites/motifs and consequently to infer recombination lifetimes.